Economic Factors Affecting the Environmental Degradation under Sustainable Development: The Case of Selected Arab Countries - Nsour, Ashraf; ALzobi, Basheer (Jordan Journal of Business Administration, 2018)
This study aims at analyzing the impact of economic growth on the environment in a number of Arab countries for the period (1985-2014). Real GDP was used as an indicator of economic growth and CO2 emissions were used as an environmental index under the Kuznets curve assumptions, in addition to energy consumption and foreign direct investment. To achieve the study objectives, the model of this study was estimated using Pedroni and Kao residual cointegration tests, which measure both long-run effects and short-run dynamics using panel Fully Modified Least Squares (FMOLS). Empirical results show that the environment variable and the economic variables became static after taking the first difference. Therefore, they are integrated in the same order, I (1). The cointegration results indicate that there are stable long-run relationships among emissions of carbon dioxide (CO2) and other economic variables. It was also found that the relationship between GDP (linear and quadratic) and emissions of carbon dioxide (CO2) is positive and inverse. In particular, the results of the analysis show that the estimated coefficients of CO2 emissions model are consistent with the EKC assumptions. In addition, the results reveal a significant effect at a significance level of 5% for energy consumption and foreign direct investment on the environment. Accordingly, the study concluded with several recommendations, the most important of which are to take environmental aspects into account in the formulation of macroeconomic policies and use environmentally clean technologies in various productive sectors.